Application of the Merchandise Inventory Accounting System at the Rejo Sari Store, Kepahiang District - Teguh Setiawan; Ummul Khair (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The scope of this research is about the Application of the Merchandise Inventory Accounting System at the Rejo Sari Store, Kepahiang District. The purpose of this study was to see the application of the inventory accounting system at the Rejo Sari Store, Kepahiang District based on PSAK No. 14 of 2009. The data analysis method used is descriptive qualitative method. The object of research includes (1) the procedure for recording the cost of goods sold (2) the procedure for recording the cost of goods sold (3) the procedure for recording the cost of goods sold returned to suppliers (4) the procedure for requesting and issuing warehouse goods (5) the procedure return of warehouse goods (6) physical inventory counting system. Research subjects include shop owners, finance department, and Warehouse department. Data collection techniques are Observation, Interview, and Documentation. The analysis technique uses a qualitative descriptive analysis technique. The results obtained show that the inventory recording system, inventory valuation method, and inventory presentation in the financial reports of Toko Rejo Sari, Kepahiang District, are not made in accordance with PSAK No. 14 of 2009. Rejo Sari Stores, Kepahiang District, should apply PSAK No. 14 of 2009 on the preparation of its financial statements. Implementing a merchandise inventory recording system by making inventory cards that are recorded both manually and by using a computerized system. Checking inventory records to avoid unwanted things such as fraud, loss and expiration.